Eimeria necatrix Infection in Chickens: Protective Immunity Induced by Immunization with the Recombinant Gametocyte Antigen EnGAM22 - Wang, Feiyan; Cao, Liqin; Xu, Jinjun; Tao, Jianping; Liu, Dandan (Acta Scientiae Veterinariae, 2025)
Background: Coccidiosis is a significant parasitic disease in poultry, leading to considerable economic losses. The macrogametocyte stage of Eimeria species has been identified as a potential target for protective immunity. Previous studies have indicated that antigens derived from this stage can provide immunity against coccidiosis. The objective of the study was to evaluate the effects of recombinant EnGAM22 vaccination on resistance to experimental E. necatrix infection and correlated disease resistance with humoral and cell-mediated immunity in Chickens. Materials, Methods & Results: To evaluate the immunogenicity of the recombinant protein rEnGAM22, chickens were subcutaneously injected with 25, 50, or 75 μg of the protein along with Freund’s adjuvant. Post-immunization, the chickens were challenged orally with sporulated Eimeria necatrix oocysts. The effectiveness of the vaccine was measured through various parameters, including fecal oocyst output, lesion scores, body weight gain, serum antibody levels, and cytokine responses. Chickens vaccinated with 50 μg of rEnGAM22 and subsequently challenged with sporulated E. necatrix oocysts showed reduced fecal oocyst shedding and lesion scores compared to other immunized groups and the infected control group, with the exception of the live oocyst group. There was no significant difference in body weight between the immunized groups and the infected control group. Additionally, rEnGAM22 induced higher levels of anti-rEnGAM22 serum antibodies, particularly 7 days after secondary immunization, especially in the 50 μg group. Serum levels of IL-2, IL-4, IL-10, and IFN-γ were highest in the group receiving 50 μg of rEnGAM22, with IL-2 and IL-4 showing a stronger response compared to IL-10 and IFN-γ. These findings suggest that rEnGAM22 provides some level of protection against E. necatrix infection and could be considered for developing a recombinant subunit vaccine against coccidiosis. Discussion: The findings of this study demonstrate that the recombinant protein rEnGAM22 from Eimeria necatrix gametocytes has the potential to confer protective immunity against coccidiosis in poultry, particularly at a dosage of 50 μg. The reduction in fecal oocyst shedding and lesion scores in chickens vaccinated with 50 μg of rEnGAM22 suggests that this dosage is optimal for eliciting an effective immune response. These results are consistent with the reported protective role of macrogametocyte stage antigens in previous studies, reinforcing the potential of targeting this stage in the lifecycle of Eimeria species for vaccine development. The study also highlights the ability of rEnGAM22 to induce a strong humoral immune response, as evidenced by the increased production of anti-rEnGAM22 serum antibodies. The significant rise in antibody levels 7 days after secondary immunization, particularly with the 50 μg dose, indicates high immunogenicity and memory response induction. This is further supported by elevated cytokine levels, especially IL-2 and IL-4, markers of Th1 and Th2 immune responses. The dominance of IL-2 and IL-4 over IL-10 and IFN-γ suggests a balanced Th1/Th2 response, which is crucial for effective immunity against intracellular parasites like Eimeria. Interestingly, there was no significant difference in body weight between the immunized groups and the infected control group, indicating that while rEnGAM22 vaccination reduces parasite load and tissue damage, it does not completely prevent the impact of infection on growth performance. This suggests that while rEnGAM22 offers some protection, it may need to be combined with other antigens or adjuvants to improve efficacy and reduce the impact of infection on poultry production. The study highlights the potential of rEnGAM22 as a recombinant subunit vaccine candidate for coccidiosis, but further research is required to optimize formulation, dosage, and assess long-term protection, including combining it with other immunogenic proteins for broader protection against multiple Eimeria species. Keywords: coccidiosis, Eimeria necatrix, gametocyte antigen, immunization, cytokines.